Meningkatkan Kemampuan Mengenal Konsep Terapung Tenggelam melalui Metode Bermain Sains pada Anak Kelompok B TK Pertiwi II Karangwuni Pringsurat Temanggung Semester II Tahun Pelajaran 2017/2018 - Siti Ngaisah (Universitas PGRI Semarang, 2021)
Introduction to science should be done from an early age with fun activities and through habituation so that children experience the scientific process directly. This is done so that children not only know the results but also can understand the process of the scientific activities they do. Science allows children to explore various objects, both animate and inanimate objects, to train children to use their five senses to recognize various symptoms of objects and events. The problem faced by children in Group B of TK Pertiwi II Karangwuni is the low ability to recognize the concept of floating and sinking. The purpose of this study was to determine the process and magnitude of the increase in the introduction of the concept of floating and sinking through the method of playing science in children in Group B of TK Pertiwi II Karangwuni Pringsurat Temanggung Semester II of the 2017/2018 Academic Year. The subjects of this study were students of Group B TK Pertiwi II Karangwuni totaling 20 children. The research was carried out from March to April 2018. The data collection methods used were observation, documentation, field notes and interviews. Based on the results of the research and discussion that has been carried out, it is concluded that the science play method can improve the ability to recognize the floating and sinking concept of children in Group B TK Pertiwi II Karangwuni Pringsurat Temanggung Semester II 2017/2018 Academic Year. Increased ability to recognize the concept of floating and sinking can be seen from the percentage of data obtained in pre-action, Cycle I and Cycle II. At the pre-action stage, most of the children were in the undeveloped criteria of 60%, in Cycle I the children's ability increased to the criteria of developing as expected by 30% or 6 children out of a total of 20 children. In Cycle II, it increased to 14 children (70%) with the assessment criteria developing as expected and 4 children (20%) developing very well. Learning is said to be successful because the ability to recognize the floating sinking concept of children through playing science has increased by more than 80% from the initial conditions before the action and is in accordance with predetermined success indicators.